Understanding (non)leadership phenomena in collaborative interorganizational networks and advancing shared leadership theory: an interpretive grounded theory study - Sigrid Endres; Jürgen Weibler (Business Research, 2020)
Despite the increasing significance of collaborative interorganizational networks, understanding of leadership phenomena in these contexts is still scarce. How, and in what form will leadership emerge in such (a priori) non-hierarchical contexts with peerlike work settings, if at all? Through an interpretive grounded theory study conducted in collaborative interorganizational networks, we found that the networks either remained at the stage of leaderless cooperation (leadership void) or developed shared leadership. We then sought to understand the underlying mechanism of collaboration that might explain the different (non)leadership phenomena. Our study's main result is the empirically grounded identification of two distinct forms of network participation with specific network identities as its core, which are related to the distinct leadership-related phenomena in our networks. (1) Task-based network identity, which includes an individualistic network identity, a single achievement motivation, and a largely instrumentalist orientation towards network participation, is related to a leadership void (non-leadership emergence, i.e. a form of leaderless cooperation). (2) Joint-motivational network identity, which includes a collectivistic network identity, joint network motivation, and a largely value-laden attitude towards network participation, is related to shared leadership. Our findings shed new light on collaboration and leadership phenomena in interorganizational networks, concurrently providing progress on conceptualizing shared leadership, in particular by introducing joint-motivational network identity as a new concept related to shared leadership development. We discuss implications for the management of collaborative interorganizational networks and advance theory on plural forms of leadership such as collective or shared leadership.
Keywords: 650; Leadership in interorganizational networks; Collective/shared leadership; Plural leadership; Self-managing/self-governing organization; Non-hierarchical context; Network identity; Interpretive grounded theory approach